1995
DOI: 10.1111/j.1469-8137.1995.tb03090.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear differentiation in the filamentous caulonema of the moss Funaria hygrometrica

Abstract: SUMMARYNuclei from difTerent eel! types in plants and animals show many features of differentiation; they differ in shape, volume, structure, ultrastructure and in the distribution of nuclear components. Using the filamentous caulonema of the moss Funaria hygrometrica Hedw. this study records the changes in cytoplasmic organization alongside the reorganization of the interphase nucleus. Events taking place in the meristematic cells at or near the tip of the ad\ ancmg caulonemal filaments {e.g, acquisition of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…8C). This suggests differentiation between the haploid genomes such that only one genome at a time replicates (92). Such specialization of component genomes may be mediated through DNA methylation or other genomic imprinting mechanism.…”
Section: Nuclear Differentiation With Polyploidymentioning
confidence: 99%
See 1 more Smart Citation
“…8C). This suggests differentiation between the haploid genomes such that only one genome at a time replicates (92). Such specialization of component genomes may be mediated through DNA methylation or other genomic imprinting mechanism.…”
Section: Nuclear Differentiation With Polyploidymentioning
confidence: 99%
“…Moss caulonemata lend themselves to developmental studies of the nucleus because cell and nuclear differentiation can be observed over time in vivo (92). Caulonemata are filaments of cells growing by cell division of an apical cell.…”
Section: Nuclear Differentiation With Polyploidymentioning
confidence: 99%
“…This paper aims at further understanding of relationships between nuclear and cytoplasmic differentiation in plant development by exploiting our recent discovery of regular and profound nuclear and cytoplasmic changes occurring during the development of moss caulonemata (Kingham et al, 1995).…”
Section: mentioning
confidence: 99%
“…During caulonemal differentiation, the nuclei endoreduplicate and elongate and their ultrastructure changes substantially. Concomitantly, the cytoplasm reorganizes, with major microtubule-associated changes in the distribution of plastids, mitochondria and endomembrane domains (Kingham et al, 1995).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation